Aspek Hukum Dalam Likuidasi Bank - Miftakhul Huda (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2021)
In this study we can analyze about, the definition of bank liquidation, duties, authorities, and responsibilities of the liquidation team, factors causing bank liquidation, aspects about the level of bank health, assessment of CAMELS factors, impact of liquidity risk on banks. The result is defined by bank liquidation. Liquidation is the ability of banks to meet their debt obligations, be able to repay all their deposits, and be able to fulfill credit requests submitted by debtors without delay. Duties, authorities, and responsibilities of the liquidation team such as registering and announcing dissolution in bank law by detailing, conducting an inventory of bank assets and liabilities in liquidation, determining the method of liquidation. The cause of bank liquidation as well as aspects concerning bank health is the result of qualitative reviews of various aspects that affect the condition or performance of a bank through quantitative assessments and or qualitative assessments of capital, asset quality, management, profitability, liquidity and sensitivity to market risk factors. The assessment of the CAMELS factor is that banks are required to carry out business activities based on the principle of caution in order to maintain or improve the soundness of the bank. Commissioners of bank directors are required to monitor and take the necessary steps so that the soundness of the bank can be met. And the last impact of liquidity risk on banks includes, the impact on shareholders, the impact on employees, the impact on customers and the impact of the economy.